A computational fluid dynamic analysis of prolonging survival in the microvascular vein grafting - Muhd Nur Rahman, Yahya
A digital artery disease in the upper extremity is uncommon to happen but the revascularization procedure is still needed. As action taken, the surgical vein bypassing or vein interposition is performed. However, one or more internal diameters of the applied Reverse Saphenous Vein Graft (RSVG) are blocked and severely narrowed due to the irregular geometry formation such as internal diameter mismatched and over the length kink after the revascularization. In previous researches, the irregular geometry formation, the size discrepancy and bent in the vessel caused the abnormal blood flow and initiated the thrombosis. Furthermore, their previous works were also supported by clinical theory. The objective of this study is to investigate the effect of the blood flow on internal diameter mismatched and over the length kink of the RSVG models that relates to their long term survival. A Three-Dimensional Computational Fluid Dynamic (3D CFD) method is employed to investigate the velocity, the pressure gradient and the Wall Shear Stress (WSS) on ideal straight and irregular geometry of the RSVG models. For this research, the pulsatile laminar blood flow demonstrates non-hydraulically flow in irregular geometry of the vein graft models compared to an ideal straight model even in a steady state laminar blood flow test. As a conclusion, the results showed high value in the velocity, the pressure gradient and the WSS in the mismatch problem but low value in the velocity, the pressure gradient and the WSS in the over length kink problem. Any abnormal blood flow behavior will initiate the formation of the thrombosis and reduce the vein graft survival.